Água, vereda, veredeiro: um estudo sobre as agriculturas camponesa e comercial, nas cabeceiras do Rio Formoso, em Buritizeiro-MG - Gama, Maria das Graças Campolina Cunha (2006)
The theme of the research aimed to study the transformations Socioenvironmental and cultural occurred in the head of the Formoso River, affluent of The São Francisco River, in the municipality of Buritizeiro, Northwestern of Minas Gerais. Until the 60s, this municipality presented a population predominantly rural and the head of the river served as a place of reproduction of the way of life and work of the peasant. With the introduction of the capitalist activities in the country, from the 70s on, charcoal production, reforestation, and commercial agriculture related to the agricultural industry the peasant families were expropriated from their land and migrated to the city, accelerating the urbanization in the municipality. The methodology was based on bibliographical review, document research, field research, open interviews and oral stories by peasant families and rural workers. The analysis of the socio-environmental impacts was made by means of the interpretation of photography images. The process of economical development in the country in the head of the Formoso River has consolidated the social inequalities, involving the peasant families and the environment, through new productions forms.